Potential of the fluoroketolide RBx 14255 against Streptococcus pneumoniae, Neisseria meningitidis and Haemophilus influenzae in an experimental murine meningitis model. (2nd May 2019) - Barman, Tarani Kanta; Kumar, Manoj; Chaira, Tridib; Gangadharan, Ramkumar; Singhal, Smita; Rao, Madhvi; Mathur, Tarun; Bhateja, Pragya; Pandya, Manisha; Ramadass, Venkataramanan; Chakrabarti, Anjan; Das, Biswajit; et al.
Abstract: Background: RBx 14255 is a fluoroketolide in pre-clinical evaluation with potent activity against MDR Gram-positive pathogens. Objectives: To investigate the efficacy of RBx 14255 against bacterial meningitis caused by Streptococcus pneumoniae, Neisseria meningitidis or Haemophilus influenzae in an experimental murine meningitis model. Methods: In vitro activity of RBx 14255 was evaluated against clinical isolates of S. pneumoniae, N. meningitidis and H. influenzae . The in vivo efficacy of RBx 14255 was evaluated against bacterial meningitis, induced with S. pneumoniae 3579 erm (B), S. pneumoniae MA 80 erm (B), N. meningitidis 1852 and H. influenzae B1414 in a murine meningitis model. Results: RBx 14255 showed strong in vitro bactericidal potential against S. pneumoniae, N. meningitidis and H. influenzae with MIC ranges of 0.004–0.1, 0.03–0.5 and 1–4 mg/L, respectively. In a murine meningitis model, a 50 mg/kg dose of RBx 14255, q12h, resulted in significant reduction of bacterial counts in the brain compared with the pretreatment control. The concentration of RBx 14255 in brain tissue correlated well with the efficacy in this mouse model. Conclusions: RBx 14255 showed superior bactericidal activity in time–kill assays in vitro and in vivo in an experimental murine meningitis model. RBx 14255 could be a promising candidate for future drug development against bacterial meningitis.